Structures of Meaning: Karel Kosík on the Subject of Culture - Landa, Ivan (Dějiny – teorie – kritika, 2017)
This article offers a reconstruction of Kosík’s materialist theory of culture. The first part outlines three ideal types of approaches to culture (anthropological, semiotic, and hermeneutic). In the second part, two important concepts of Kosík’s materialist theory of culture are discussed: the notion of ‘concrete totality’ and the idea of a ‘worldview’. The third part of the article reformulates Kosík’s objections against the substitution thesis, according to which a culture can function as a substitute of real political opposition. In the fourth part, the author explains the distinction between a piece of work and an artefact. In the fifth step, he analyses the way in which Kosík uses the distinction between a piece of work and an artefact in formulating his argument against explanatory reductionism (sociologism and economism) and how he applies them in his proposed revision of the classical theory of reflection. The sixth part focuses on the issue of creation of epistemic values in connection with the process of ‘typification’ of individual experience. The seventh and final part then addresses the question to what extent Kosík’s theory of culture should be characterised as materialist.